POLA DAKWAH MULTIKULTURAL DI INDONESIA - Syamsuri, Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 9 No 1 (2013), 2013)
Muhammadiyah (born 1920) and Nahdlatul Ulama (NU, born 1920) is a missionary organization that dissolves as reconciler Indonesian culture. The second organization is an accumulation of da'wah trip, which lasted from seventh century. Muhammadiyah chose Maliki's teaching (mazhab) and NU chose Shafi'i teachings as a corridor for mass worship. Acculturation propaganda in understanding the situation and condition of Indonesia, which encourages the flourishing of Islamic broadcasting now re-piqued because of the influx of transnational Islamic ideology. Foreign Islamic movements like the Muslim Brotherhood, Salafi, Hizb ut-Tahrir, Jama'ah Tabliq, Syi'i, and others, made amotion Indonesia as da'wah activities movement. The lears of mazhab who have different views with other mazhab leaders, however never blame the other view. Khilafiyah problems (differences of opinion) in religious life for a few priests in the schools is a scientific things to grow up the dynamics of science. Praxis differences caused bloodshed, not a religious event, but it is a human tragedy that use religious arguments to justify its actions.